Hubungan Asupan Purin dan Lingkar Pinggang dengan Kadar Asam Urat Pada Pralansia dan Lansia di Puskesmas Gamping Ii Sleman - Widodo, Monicha Wenny Pertiwi; Fayasari, Adhila (Poltekkes Kemenkes Pontianak, 2025)
Background: Hyperuricemia is still a problem in the elderly in Yogyakarta, ranking 23rd out of 34 provinces. The causes are high purine foods, obesity, alcohol, physical activity, gender, and genetics. So it is necessary to conduct research on purine intake and waist circumference with uric acid levels in the elderly and elderly. Objectives: To analyze the relationship between waist circumference and purine intake with uric acid levels in the elderly and the elderly in the working area of Puskesmas Gamping II. Methods: This study used a cross-sectional design on 103 pre-elderly and elderly people in Gamping, Yogyakarta. The data taken were primary data in the form of respondent identity, high purine food data, waist circumference data and uric acid level data. The instruments used were SQ-FFQ questionnaire, metline tape, and Auto Check tool, Data were analyzed using chi-square with α 5%. Results: Results of univariate analysis of waist circumference at risk 71.8%, high purine intake 41.7%, and high uric acid levels 43.7%. There is no relationship between waist circumference waist circumference with uric acid levels p = 0.461 and there is a relationship between purine intake and uric acid levels p = 0.036. with uric acid levels p = 0.036. Conclusion: There is a relationship between purine intake and uric acid levels. Need education about high purine foods.